Tinjauan Kriminologis Terhadap Perilaku Perundungan pada Kalangan Pelajar di Kabupaten Wajo - Martono; Mustari; Saskia Dwi Anggaraeni; Desriana Maharani; Iswandar; Ardi Ansyah; Gusti (YP-SDI Lamaddukelleng, 2024)
Bullying cases in the form of bullying and physical violence that occur in the world of education, both by educators and fellow students. This study aims to determine the factors that cause bullying behavior among students and to determine what efforts are made by educators and students to prevent and overcome bullying behavior in educational institutions. The data collection technique used by the author is observation, namely data collection carried out directly by observing the objects being studied. Questionnaire, namely a data collection technique by providing a list of questions to respondents. Documentation, namely data collection using documents concerning legislation, literature books that are related to this study, The data analysis technique used is primary data and secondary data analyzed qualitatively and then presented descriptively, namely explaining, describing, and describing according to the problems related to this study. The results of this study indicate that bullying behavior among students in Wajo Regency is caused by social or economic status factors, social environment, social media, family environment, biological factors, and thinking. And the efforts made to prevent bullying behavior are pre-emptive efforts, repressive efforts, and preventive efforts